An exploratory study of school district adaptation - Berman, Paul, 1937-; McLaughlin, Milbrey Wallin; Pincus, John A.; Weiler, Daniel M.; Williams, Richard C.; Rand Corporation; National Institute of Education (U.S.) (Santa Monica, CA : RAND, 1979)
The literature suggests that school districts "innovate" yet do not change in significant ways. This study explains such behavior in terms of organizational dynamics, not the characteristics of a planned change effort. The adaptation of an innovation can be a defense mechanism. During implementation, an innovation is adapted to reinforce rather than replace existing patterns. The same organizational conditions perpetuate the illusion that change is occurring. To explore these issues, five school districts were examined for internal and external pressures for change. The characteristic behavior, or stable states, of school districts can be categorized by one of two ideal types: maintenance or development. They do not, of course, fully capture the realities of school district life, but underlying organizational patterns in these stable states define limits as well as possibilities for successfully implementing and sustaining planned change efforts in local school systems.
"May 1979."
Includes bibliographical references (p. 65-69).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: School districts -- United States; School management and organization -- United States